Non-noble metallic nanoparticles supported on titania spheres as catalysts for hydrogen generation from hydrolysis of ammonia borane under ultraviolet light irradiation. (23rd August 2018) - Yang, X.J.; Wang, C.Y.; Gao, R.Y.; Lu, Z.M.; Zhang, X.H.; Yu, X.F.; Li, L.L.
Abstract: Herein, a report on non-noble metal (Ni, Co, Cu, and their combination) nanoparticles (NPs) supported on TiO2 spheres as catalysts for hydrogen generation via hydrolysis of ammonia borane (NH3 BH3, AB) is provided. The TiO2 spheres were prepared through a template method by using polystyrene (PS). The metallic nanoparticles were synthesized by a redox replacement reaction. The structure, morphology, and chemical composition of the obtained samples were analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) equipped with energy dispersive X-ray spectroscopy (EDX), and X-ray Photoelectron Spectroscopy (XPS). The characterization results showed that the metallic nanoparticles were well dispersed on the TiO2 supports. The catalytic activity toward the hydrolysis of AB was found to correlate well with the amount of metallic elements in catalysts while for the multicomponent phases, a synergistic effect was noticed. Theoretical calculations revealed that Ni, Co, and Cu atoms significantly influenced the electronic behavior of TiO2 and thereby, the catalytic properties of the materials. Highlights: Ni0.3 Co0.3 Cu0.4 /TiO2 for hydrogen generation via hydrolysis of AB. NiCoCu/TiO2 activity was correlate with the amount of metallic elements. The calculations revealed metal atoms influenced the electronic behavior of TiO2.